107k views
5 votes
Given the equation p=s1 t-s2 t , which equation is solved for t?

User Morph
by
4.9k points

2 Answers

4 votes

Answer:


t=(p)/((s_1-s_2))

Explanation:

We have been given an equation
p=s_1t-s_2t. We are asked to solve our given equation for t.

First of all, we will factor out t from right side of our given equation as:


p=t(s_1-s_2)

Now, we will switch sides as:


t(s_1-s_2)=p

Finally, we will divide both sides of our equation by
(s_1-s_2).


(t(s_1-s_2))/((s_1-s_2))=(p)/((s_1-s_2))


t=(p)/((s_1-s_2))

Therefore, the value of t for our given equation would be
(p)/((s_1-s_2)).

User Rameshthoomu
by
5.3k points
4 votes

Answer:


t=(p)/(s_1-s_2)

Explanation:

Assuming the "1" and "2" are subscripts, we can write the problem as following:


p=s_1t-s_2t

In order to solve for t, we need to isolate it first and then do algebra. The steps are shown below:


p=s_1t-s_2t\\p=t(s_1-s_2)\\t=(p)/(s_1-s_2)

User Gal Sisso
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.